Experimental study on shear behavior of tie-bars in steel-plate concrete composite structure subjected to cyclic loading. (15th May 2018) - Zhai, Changhai; Lu, Bing; Wen, Weiping; Ji, Duofa; Xie, Lili
Highlights: This paper studies the shear behavior of tie-bars under cyclic loading. The failure modes, load-slip curves and shear stiffness are investigated. The effects of load type and tie-bar diameter on the shear behavior are studied. The effect of welded joint structural type on the shear behavior is studied. Abstract: Tie-bars play an important role in the transfer of the shear between the steel faceplate and the concrete in steel-plate concrete composite structure. Twelve push-out specimens were tested to investigate the shear behavior of tie-bars subjected to monotonic and cyclic loadings in high strength concrete. The primary parameters analyzed in this study included tie-bar diameter, tie-bar strength grade, load procedure and welded joint structural type. The failure modes, shear capacities, shear slips, load-slip curves, shear stiffness, ductility, energy dissipation capacities and tensile strain distributions of tie-bars were studied, in addition to comparing the ultimate shear capacities of tie-bars in this experiment with those calculated by an existing formula. The experimental results indicated that the groove fillet welding significantly improved the shear capacities of tie-bars under cyclic loading with respect to other three welded joint structural types in this experiment (The difference is more than 33%). The shear capacity, shear stiffness and shear slip increased significantly with the increase of tie-bar diameter. The tie-bars subjected to cyclic loading exhibited lower shear capacities and shear slips than those under monotonic loading. The reductions of the shear capacity and the shear slip decreased approximately with the increase of tie-bar diameter, and they were 28–42% and 58–67%, respectively. The tensile strain distributions of tie-bars were affected significantly by the load procedure, and according to the distributions, two recommendations were proposed for the design for out-of-plane shear capacity of steel-plate concrete composite structure subjected to bending moment.